Legal Protection For Foreign Medical Personnel According To Law No. 17 Of 2023 Concerning Health - Juliyanti Tjua; Erikson Sihotang; Ni Ketut Wiratny (International Journal Labs, 2024)
Legal protection for foreign doctors/doctors in carrying out their profession refers to Article 273 and Article 291 (1) of the Health Law. Article 291 paragraph (1) if you comply with professional standards, service standards, rational procedural standards and professional ethics, taking into account the patient's health needs, organizational culture in the hospital or medical institution where the doctor works. Doctors' responsibilities towards patients refer to statutory provisions, including legal, administrative and ethical responsibilities.